Domestic violence against women and associated factors in Ethiopia; systematic review - Semahegn, Agumasie (Reprod Health, 2015)
BACKGROUND: Violence against women is now widely recognized as a serious human right abuse, and an important public health problem with substantial consequences physical, mental, sexual, and reproductive health. Data on systematic review of domestic violence are needed to support policy and program recommendations. Therefore, the overall purpose of this systematic review was to assess magnitude of domestic violence against women and associated factors in Ethiopia. METHODS: Studies systematically reviewed in Federal Democratic Republic of Ethiopia from 2000 to 2014. Systematic review was employed on published research works from databases such as Pubmed, popline, Hinari, and Google using key words. We also consulted public health experts. Community based studies with a study population (15–49 years) were included for review. Thirteen peer reviewed papers and two consecutive Ethiopian demographic and health surveys (2005 and 2011) were included to the systematic review. Twenty seven available in open access journals were retrieved and assessed based on the criteria’s such as community based study, cross sectional study design, clearly report prevalence and associated factors were included in the systematic review work. Finally, 15 papers were included in this review. RESULTS: Lifetime prevalence of domestic violence against women by husband or intimate partner among 10 studies ranged from 20 to 78 %. The lifetime domestic physical violence by husband or intimate partner against women ranged from 31 to 76.5 %. The life time domestic sexual violence against women by husband or intimate partner ranged from 19.2 to 59 %. The mean life time prevalence of domestic emotional violence was 51.7 %. Significant number of women experienced violence during their pregnancy period. Domestic violence against women significantly associated with alcohol consumption, chat chewing, family history of violence, occupation, religion, educational status, residence and decision making power. CONCLUSION: Domestic violence against women was relatively high in different parts of Ethiopia. Domestic violence has direct relationship with sociodemographic characteristics of the victim as well as perpetrator. Therefore, appropriate health promotion information activities needed to tackle associated factors of domestic violence against women or to prevent and control the problem to save women from being victim.